Penanganan bedah tumor sel mast digital pada anjing betina ras campuran geriatrik - Ethan Low Chiew Yong; Shiv Kumar Singh (ARSHI Veterinary Letters, 2026)
Digital mast cell tumours (MCTs) in dogs present a surgical challenge because their acral location often limits the achievement of adequate oncologic margins. This report describes the clinical presentation, surgical management, and histopathological confirmation of a digital MCT in an geriatric dog. A 15-year-old mixed-breed female dog weighing 7.6 kg was presented with a mass in the interdigital region of the limb. Clinical examination revealed that the dog remained active, with no obvious abnormalities in posture or gait. Because digital mast cell tumors (MCTs) are difficult to manage surgically owing to limited tissue for adequate margins, surgical excision was selected. Intraoperatively, the mass was found to extend around digit IV, requiring complete excision with digit amputation. Histopathological examination confirmed the presence of a mast cell tumour with infiltrative neoplastic mast cell proliferation. Postoperative management included wound cleansing, modified Robert Jones bandaging, amoxicillin-clavulanate, prednisolone, and topical hypochlorous acid-based wound care